Transcription activator like effector (TALE)-directed piggyBac transposition in human cells - Owens, Jesse B. (Oxford University Press, 2013)
Insertional therapies have shown great potential for combating genetic disease and safer methods would undoubtedly broaden the variety of possible illness that can be treated. A major challenge that remains is reducing the risk of insertional mutagenesis due to random insertion by both viral and non-viral vectors. Targetable nucleases are capable of inducing double-stranded breaks to enhance homologous recombination for the introduction of transgenes at specific sequences. However, off-target DNA cleavages at unknown sites can lead to mutations that are difficult to detect. Alternatively, the piggyBac transposase is able perform all of the steps required for integration; therefore, cells confirmed to contain a single copy of a targeted transposon, for which its location is known, are likely to be devoid of aberrant genomic modifications. We aimed to retarget transposon insertions by comparing a series of novel hyperactive piggyBac constructs tethered to a custom transcription activator like effector DNA-binding domain designed to bind the first intron of the human CCR5 gene. Multiple targeting strategies were evaluated using combinations of both plasmid-DNA and transposase-protein relocalization to the target sequence. We demonstrated user-defined directed transposition to the CCR5 genomic safe harbor and isolated single-copy clones harboring targeted integrations.